Effect of pre-ozonation-enhanced coagulation on dissolved organic nitrogen in municipal wastewater treatment plant effluent. Issue 20 (6th September 2019) - Liu, Bing; Gu, Li; Li, Qingfei; Yu, Guozhong; Zhao, Chengmei; Zhai, Huimin
ABSTRACT: Municipal wastewater treatment plant (WWTP) effluent is increasingly used as reclaimed water and as water sources for downstream areas. Effluent dissolved organic nitrogen (DON) is considered to be the precursor to nitrogen disinfection by-products (N-DBPs). Here, we investigated DON removal by pre-ozonation-enhanced coagulation and found that (1) pre-ozonation significantly enhanced the removal of DON, dissolved organic carbon (DOC), and UV254 by coagulation. (2) pH had an important impact on the pre-ozonation-enhanced coagulation. At lower pH, the removal of DON, DOC, and UV254 is higher. (3) As ozone dosage increased, zeta potential gradually increased, while dissolved calcium concentrations declined and there was a strong correlation between zeta potential and dissolved calcium concentrations. (4) Small (<6 kDa) molecular weight DON was dominant in the effluent. Hydrophilic and hydrophobic DON accounted for 58.5% and 30.8% of the total, respectively. (5) Coagulation reduced overall DBP formation potentials to less than 20%. In contrast, overall DBP formation potentials increased after ozonation. However, pre-ozonation-enhanced coagulation not only removed 71% DON, but also reduced overall DBP formation potentials by more than 40%. (6) 3-DEEM spectra indicated that DBP formation potentials and DON concentrations were related to three main peaks, which corresponded to tryptophan-based proteins, aromatic proteins, and fulvic acids.